Comparison of perioperative and short‐term oncological outcomes after single‐ or multiport surgery for colorectal cancer. (July 2015) - Tei, M.; Wakasugi, M.; Akamatsu, H.
Abstract Aim The aim of this retrospective study was to compare the short‐term surgical results of single‐port surgery (SPS) with those of multiport surgery (MPS) for colorectal cancer. Method We studied 673 consecutive patients who underwent SPS or MPS for colorectal cancer in our department from January 2008 to December 2013. The operative parameters and oncological outcome were analysed and compared between the SPS and the MPS groups retrospectively. Results The SPS and MPS groups did not differ significantly in terms of preoperative evaluation. The median operative time was significantly shorter with SPS than with MPS (176 min vs 193 min; P < 0.001). The two groups did not differ significantly in terms of postoperative complications. Length of hospital stay was significantly shorter with SPS than with MPS (8 days vs 10 days; P < 0.001). Oncological resection was similar in the two groups. The disease‐free survival rates at 2 years according to the TNM stage did not differ significantly between the two groups (Stage I, 98.5% vs 94.7%; Stage II, 93.4% vs 90.7%; and Stage III, 70.8% vs 68.4%). Conclusion Our experience demonstrates that SPS is safe and can provide oncological outcomes equal to those of MPS in patients with colorectal cancer.